GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 14 Dec 2019, 10:54

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# If yz – zx = 3 and zx – xy = 4, then xy – yz =

Author Message
TAGS:

### Hide Tags

Math Expert
Joined: 02 Sep 2009
Posts: 59725
If yz – zx = 3 and zx – xy = 4, then xy – yz =  [#permalink]

### Show Tags

07 Apr 2019, 21:04
00:00

Difficulty:

25% (medium)

Question Stats:

70% (01:00) correct 30% (01:41) wrong based on 10 sessions

### HideShow timer Statistics

If yz – zx = 3 and zx – xy = 4, then xy – yz =

(A) –7

(B) 1

(C) 3

(D) 4

(E) 7

_________________
VP
Joined: 31 Oct 2013
Posts: 1492
Concentration: Accounting, Finance
GPA: 3.68
WE: Analyst (Accounting)
Re: If yz – zx = 3 and zx – xy = 4, then xy – yz =  [#permalink]

### Show Tags

07 Apr 2019, 21:11
1
Bunuel wrote:
If yz – zx = 3 and zx – xy = 4, then xy – yz =

(A) –7

(B) 1

(C) 3

(D) 4

(E) 7

Given,

yz – zx = 3
zx – xy = 4
..............................
yz - xy = 7................adding both equations

xy - yz = -7..................Multiply by -1.

Senior Manager
Joined: 25 Feb 2019
Posts: 335
Re: If yz – zx = 3 and zx – xy = 4, then xy – yz =  [#permalink]

### Show Tags

07 Apr 2019, 21:15
IMO A ,

add both the equations we get xy - yz = 7

multiply both side by -1

we get the required expression

Posted from my mobile device
Intern
Joined: 23 Sep 2018
Posts: 2
Re: If yz – zx = 3 and zx – xy = 4, then xy – yz =  [#permalink]

### Show Tags

07 Apr 2019, 21:18
1. yz - zx = 3
Rearranging terms : yz = zx+3

2. zx - xy = 4
Rearranging terms : xy = zx - 4

2-1 -> xy - yz = (zx - 4) - (zx + 3) -> -7

Intern
Joined: 01 Apr 2019
Posts: 1
Re: If yz – zx = 3 and zx – xy = 4, then xy – yz =  [#permalink]

### Show Tags

07 Apr 2019, 21:22
Given
Yz-zx=3
Yz=3+zx
Also
Zx-xy=4
Zx=4+xy
Then,
Yz=3+zx
Yz=3+4+xy
Yz=7+xy
-7=xy-yz

Posted from my mobile device
Re: If yz – zx = 3 and zx – xy = 4, then xy – yz =   [#permalink] 07 Apr 2019, 21:22
Display posts from previous: Sort by